Language of Cursing and its Effect on the Community, Family and Schools - Basnet, Gopal (Journal of NELTA Koshi (JoNK), 2024)
This article deals with the language of cursing and its effects in schools and society. Being based on the observation and interviews, the study enlisted typical examples of language of cursing in the rural Nepal, and discusses their impacts on community, schools and families. It also explains the cursing words and further presents why people curse in society. The study concludes with the fact that language of cursing might have both positive as well as negative impacts and the user need to be careful while using them according to the context, participants and its effects. The teachers, administrators and all the concerned might be beneficial by understanding prevalent language of cursing.